2019
DOI: 10.1186/s12955-019-1257-z
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of Amharic version of EORTC QLQ-C30 and QLQ-BR23 modules for assessing health-related quality of life among breast cancer patients in Ethiopia

Abstract: BackgroundBreast cancer is the most common cancer among women and it affects quality of life of those women. So far, the two most frequently used tools for assessing health related quality of life in breast cancer patients, EORTC QLQ-C30 and EORTC QLQ-BR23 modules, were not validated in Ethiopia. Hence, the present study aimed to assess the psychometric properties of the tools among Ethiopian breast cancer patients.MethodsInstitutional based longitudinal study was conducted from January 1 to May 1, 2017 GC at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 19 publications
2
18
2
Order By: Relevance
“…The most obvious scaling failure was observed for the systematic therapy side effect. This might have occurred because systematic therapy side effects are often nonspeci c. This is in contrast to a previous study performed on breast cancer patients [10].…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…The most obvious scaling failure was observed for the systematic therapy side effect. This might have occurred because systematic therapy side effects are often nonspeci c. This is in contrast to a previous study performed on breast cancer patients [10].…”
Section: Discussioncontrasting
confidence: 58%
“…The breast symptom and arm symptom scales also had strong correlations with the pain scale of the QLQ-C30. A similar study performed in Turkey showed strong correlations between the symptom scales of QLQ-BR23 and QLQ-C30 [10,31]. This might be explained by the two dimensions being conceptually related.…”
Section: Modi Cation and Model Tmentioning
confidence: 84%
See 1 more Smart Citation
“…The cognitive function scale displayed a Cronbach's alpha of 0.50 for the English version and of 0.66 for the Luganda version. A low alpha coefficient for the cognitive scale has been reported in other studies in East Africa [7,12,30]. It has been argued that this may to some extent be due to the small number of items in the scale.…”
Section: Discussionmentioning
confidence: 81%
“…The questionnaire is applicable in more than 70 countries worldwide including the major languages spoken in the Western world and Asia [9]. In Sub-Saharan Africa, the questionnaire is available in 9 languages: Afrikaans, Amharic, Ilokano, Kiswahili, Sepedi, Sotho, Xhosa, Yoruba and Zulu [9][10][11][12]. In Uganda no valid and reliable instrument for assessment of generic HRQoL in adults with cancer exists.…”
mentioning
confidence: 99%